Advanced accounting - Griffin, Charles H.; Williams, Thomas H. ;Larson, Kermit D. ;Boatsman, James R. ;Bell, Timothy B. (Homewood, Illinois : Irwin Inc., 1985)
In writing this fifth edition of Advanced Accounting, we have attempted to retain features from the fourth edition which adopters have found helpful. In the two units dealing with business combinations and consolidated financial statements, application of the "full" equity method continues to be the reference point for discussion. This approach reflects the fundamental principles underlying consolidation without the distraction of specific working paper techniques, and is presumed to be the dominant method encountered in practice. However, recognizing that the reader may encounter situations in which the investment is carried under the cost method, discussion of the changes in parent company entries and working paper techniques necessitated by application of this method has been continued.
Unit One. Accounting for Combined Corporate Entities -- Unit Two. Consolidated Statement: An Expanded Analysis -- Unit Three. Accounting for Partnership -- Unit Four. Fiduciary and Institutional Accounting.
Includes index.